Association of microRNA-7 and its binding partner CDR1-AS with the prognosis and prediction of 1(st)-line tamoxifen therapy in breast cancer - Uhr, K. (Sci Rep, 2018)
The large number of non-coding RNAs (ncRNAs) and their breadth of functionalities has fuelled many studies on their roles in cancer. We previously linked four microRNAs to breast cancer prognosis. One of these microRNAs, hsa-miR-7, was found to be regulated by another type of ncRNA, the circular non-coding RNA (circRNA) CDR1-AS, which contains multiple hsa-miR-7 binding sites. Based on this finding, we studied the potential clinical value of this circRNA on breast cancer prognosis in a cohort based on a cohort that was previously analysed for hsa-miR-7 and in an adjuvant hormone-naïve cohort for 1(st)-line tamoxifen treatment outcomes, in which we also analysed hsa-miR-7. A negative correlation was observed between hsa-miR-7 and CDR1-AS in both cohorts. Despite associations with various clinical metrics (e.g., tumour grade, tumour size, and relapse location), CDR1-AS was neither prognostic nor predictive of relevant outcomes in our cohorts. However, we did observe stromal CDR1-AS expression, suggesting a possible cell-type specific interaction. Next to the known association of hsa-miR-7 expression with poor prognosis in primary breast cancer, we found that high hsa-miR-7 expression was predictive of an adverse response to tamoxifen therapy and poor progression-free and post-relapse overall survival in patients with recurrent disease.